Grandes obras para pequenos leitores: Portugal Pequenino de Raul Brandão e Maria Angelina Brandão em contexto das Humanidades Digitais = Great works for young readers: Portugal Pequenino by Raul Brandão and Maria Angelina Brandão in the context of Digital Humanities - Lage, Otília (2022)
An experimental and prospective study of educational extension is presented that mobilizes a descriptive analysis, from the perspective of cultural and environmental heritage, of the bridge-book for children and adults, Portugal Pequenino by Raul Brandão and Maria Angelina Brandão, with a view to the production of content for a mobile digital application. Building on from prior investigative experience of the authors in the development of the exploratory project "Raul Brandão and intergenerational relations at the digital humanities interface", it aims to develop a new dimension of this initiative. It consists of a brief approach to the literature review of the transdisciplinary area Digital Humanities in Portugal, the theoretical-methodological framework of which that underpins the study presented. Digital Humanities has managed to bring together a community of researchers that tends to grow and assert itself (Alves, 2016 a) and b), albeit in a global mapping, with regard to Portuguese-speaking heritages, the performance is lower than that of other traditions and cultures, namely Anglo-Saxon (Pereira, 2015: 110-140). However, under the impact of the increasing consolidation of the inter/transdisciplinary area of Digital Humanities on an international scale, this new field of research in Portugal has been gradually growing into a broader movement of renewal of discourses and practices of affirmation and integration of digital media transversal to the Humanities and Social Sciences.